Hodnotová orientácia Economic Value Added-EVA - Glova, Jozef (Univerzita Pardubice, 2006)
The submitted article presents EVA's value-based orientations analyze based on a survey of North-American public companies. Research was supported by SPSS analytical tools. We call in question the proclaimed best value-orientation of EVA than traditional performance measures in explaining Equity Market Value expressed by Market Value Added. The major scientifically contribution of your study is the analysis of the value-based orientation - information content regarding Operating Income, Weighted Average Cost of Capital and EVA, based on a sample of 852 North-American public companies during the period from 1988 to 1997. The sample's data has been chosen from The 2003 EVA/MVA Annual 1000 Ranking Database. The main results suggest that EVA does not have more value-orientation than traditional performance measures in explaining Equity Market Value. The relationship between EVA and Market Value Added, however, is statistically significant.
Keywords: přidaná hodnota; Economic Value Added; ukazatel EVA; Regresní analýza; korelační analýza; hodnotová orientace